Career preferences of final year medical students at a medical school in Kenya – a cross sectional study - Dossajee, Hussein; Obonyo, Nchafatso; Ahmed, Syed Masud (© 2016 BMC Medical Education, 2017)
This article was published in the BMC Medical Education [© 2017 by Dossajee et al.] and the definite version is available at : https://doi.org/10.1186/s12909-016-0528-1. The Journal's website is at: https://bmcmededuc.biomedcentral.com/articles/10.1186/s12909-016-0528-1